Gestational weight gain according to Institute of Medicine recommendations in relation to infant size and body composition. Issue 5 (17th December 2014) - Henriksson, P.; Eriksson, B.; Forsum, E.; Löf, M.
Summary Background Intrauterine life may be a critical period for programming childhood obesity; however, there is insufficient knowledge concerning how gestational weight gain (GWG) affects infant fat mass (FM) and fat‐free mass (FFM). Objectives The aim of this study was to investigate relationships between GWG according to Institute of Medicine (IOM) recommendations and infant size, FM and FFM. We also investigated if the associations were different for normal‐weight and overweight/obese women. Methods This study included 312 healthy Swedish mother–infant pairs. Infant body composition at 1 week of age was assessed using air‐displacement plethysmography. Maternal GWG was defined as below, within or above the 2009 IOM recommendations. Multiple regression analyses were used. Results Compared with women whose weight gain was within IOM recommendations, women with weight gain below the recommendations had infants that were shorter (−0.7 cm, P = 0.008) when adjusting for confounders. Normal‐weight women exceeding IOM recommendations had infants with higher FM (+58 g, P = 0.008) compared with normal‐weight women who gained within the recommendations. No corresponding association was observed for overweight/obese women. Conclusions Inadequate GWG was associated with shorter infants, while excessive GWG was associated with greater infant FM for women who were of normal weight before pregnancy.